Конституционные Права Работников На Правовую Защиту И Определенность (Constitutional Rights of Workers in Obtaining Protection and Legal Certainty) - Nur Rohim Yunus; Annissa Rezki; RR Dewi Anggraeni (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2020)
Abstract:There are so many conflicts between companies and workers, and these conflicts often end up in court. At certain moments workers are declared winners and the company is obliged to pay the right to obligations as a provider of labor. Workers hope to receive all rights and be protected by law which can overshadow and protect the existence of workers, both individually and as a group. This research uses descriptive qualitative research methodology and refers to the 1945 Constitution of the Republic of Indonesia as the main legal foundation and other laws and regulations.Keywords: Legal Protection, Constitutional Rights, Workers' Rights Аннотация:Существует много конфликтов между компаниями и работниками, и эти конфликты часто заканчиваются в суде. Бывают случаи, когда работники объявляются победителями, и компания обязана оплачивать права по обязательствам как работодатель. Рабочие надеются получить все свои права и быть защищены законом как индивидуально, так и в составе группы. В этом исследовании используется описательно-качественная методология исследования и упоминается Конституция Индонезии 1945 года в качестве основного правового закона и другие законодательные акты, представленные ниже.Ключевые слова: Правовая защита, Конституционные права, Права работников